Two-Dimensional Cr5Te8@Graphite Heterostructure for Efficient Electromagnetic Microwave Absorption - Qin, Liyuan; Guo, Ziyang; Zhao, Shuai; Kong, Denan; Jiang, Wei; Liu, Ruibin; Lv, Xijuan; Zhou, Jiadong; Shu, Qinghai (Nano-Micro Letters, 2023)
Two-dimensional (2D) transition metal chalcogenides (TMCs) hold great promise as novel microwave absorption materials owing to their interlayer interactions and unique magnetoelectric properties. However, overcoming the impedance mismatch at the low loading is still a challenge for TMCs due to the restricted loss pathways caused by their high-density characteristic. Here, an interface engineering based on the heterostructure of 2D Cr5Te8 and graphite is in situ constructed via a one-step chemical vapor deposit to modulate impedance matching and introduce multiple attenuation mechanisms. Intriguingly, the Cr5Te8@EG (ECT) heterostructure exhibits a minimum reflection loss of up to − 57.6 dB at 15.4 GHz with a thin thickness of only 1.4 mm under a low filling rate of 10%. The density functional theory calculations confirm that the splendid performance of ECT heterostructure primarily derives from charge redistribution at the abundant intimate interfaces, thereby reinforcing interfacial polarization loss. Furthermore, the ECT coating displays a remarkable radar cross section reduction of 31.9 dB m2, demonstrating a great radar microwave scattering ability. This work sheds light on the interfacial coupled stimulus response mechanism of TMC-based heterogeneous structures and provides a feasible strategy to manipulate high-quality TMCs for excellent microwave absorbers. Highlights: 1 A Cr5Te8@expanded graphite heterostructure is fabricated by chemical vapor deposition, exhibiting remarkable microwave absorption performance with a minimum reflection loss of up to − 57.6 dB at a thin thickness of only 1.4 mm under a low filling rate of 10%. 2 Density functional theory calculations deeply reveal the polarization loss mechanism triggered by heterogeneous interfaces. 3 The heterostructure coating displays a remarkable radar cross section reduction of 31.9 dB m2, demonstrating a great electromagnetic microwave scattering ability and radar stealth capability.